Symptomatic Bradycardia In CAD Patient: Which One First To Treat? - Aloysius Yuwono Suprapta; Mohammad Saifur Rohman; Ardian Rizal; Sasmojo Widito (Heart Science Journal, 2022)
Background: The incidence of sinus node dysfunction (SND) increases with age. Likewise, the incidence of coronary artery disease (CAD) has increased from year to year in Indonesia. When doctors are faced SND patients with CAD, it can be confusing in determining initial treatment options.Objective: This study aimed to describe the diagnosis and management of SND in CAD patient.Case Presentation: We will discuss a 75 years old male who had schedule to management of bradycardia symptomatic related to SND. Five month before admission, he had acute coronary syndrome, and had 2 DES implantation at left main (LM) to proximal left anterior descendent (LAD) artery and mid LAD. Two month after PCI he felt near syncope with bradycardia. Evaluation with ambulatory EKG was performed with result of SND, and correction of reversible cause related to SND already done. Eventually, symptom still exist and PPM insertion was decided to perform.Conclusion: Patients with SND and CAD have a higher risk of complications and death. Correction of reversible factors, one of which is CAD, can be done as an initial step in the treatment of SND. When symptomatic signs still appear after correction of reversible causes, PPM implantation is the modality of choice in management.